ГЛОБАЛЛАСЫЎ ДӘЎИРИНДЕ ӘДЕБИЯТ МӘСЕЛЕЛЕРИ - Торткулбаева, Т.А. (SCIENCE and SOCIETY, 2025)
This article examines the impact of the globalization process on contemporary literature and the problems arising from it. In the context of globalization, the future of national literature, ways to preserve its identity, and the role of contemporary writers are analyzed. Attention is also paid to the transformation of literature in the digital environment, translation, language policy, and the influence of new media.